2021
DOI: 10.1002/lol2.10217
|View full text |Cite
|
Sign up to set email alerts
|

Does salinization impact long‐term Daphnia assemblage dynamics? Evidence from the sediment egg bank in a small hard‐water lake

Abstract: Salinization of freshwater ecosystems threatens global aquatic biodiversity. There is a need for studies that follow populations in situ during salinization to understand the effects on species and ecosystems. We follow 170 years of Daphnia dynamics in the sediment ephippia archive of a small urban lake near St. Paul, Minnesota, to characterize effects of severe recent salinization on lake Daphnia. We found modest changes in the flux of ephippia in this lake; all three key Daphnia functional groups remained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 44 publications
1
19
1
Order By: Relevance
“…Salinization in TL is ongoing and likely started in the mid-20 th century with the onset of widespread use of road deicing salts (53). The sediment intervals from which we recovered the deepest samples reflect a period of change in the sediment egg bank (e.g., low ephippial fluxes) that have been previously reported (30), and suggest a period of rapid environmental change in this lake. However, because we were unable to hatch eggs from before the mid-1990s in TL, it is impossible to determine if the structuring we observed was ongoing or more sudden.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Salinization in TL is ongoing and likely started in the mid-20 th century with the onset of widespread use of road deicing salts (53). The sediment intervals from which we recovered the deepest samples reflect a period of change in the sediment egg bank (e.g., low ephippial fluxes) that have been previously reported (30), and suggest a period of rapid environmental change in this lake. However, because we were unable to hatch eggs from before the mid-1990s in TL, it is impossible to determine if the structuring we observed was ongoing or more sudden.…”
Section: Discussionsupporting
confidence: 73%
“…One issue threatening many f reshwater ecosystems is salinization due to human activities (26), within northern temperate lakes specif ically salinization is particularly acute (27,28). The causes and scope of salinization have been well known (29,30), while more recent studies have f ocused on deciphering the ecological impacts of salinization (31,32). In addition, we lack a more general understanding of this widespread environmental issue f rom an evolutionary perspective, and of the specif ic genetic architecture of adaptative responses.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for this positive effect is that the zooplankton communities from the associated ecozones (Boreal Cordillera, Taiga Cordillera and Taiga plains) were dominated by Leptodiatomus species (Paquette et al 2021), which are considered to be salt-tolerant taxa owing to their marine origin (Sarma et al 2006). Nationwide, however, we observed that increased sodium concentrations were more strongly associated with D. pulicaria, a species known to be relatively resilient to high salinity (Wersebe et al 2021) and which dominated in the agricultural region of the Prairies (Hudson Bay basin). We suspect that these regional patterns inhibited the detection of a nationwide negative response pattern in more urban sites where road salt is added in high quantities.…”
Section: Zooplankton Response To Water Quality Metricsmentioning
confidence: 74%